Incidencia de la lectorescritura en el rendimiento escolar de los estudiantes del tercer año de educación general básica de la Escuela José Gilberto Vaca, del recinto San Antonio, Parroquia Catarama, Cantón Urdaneta, Provincia de Los Ríos - Guapulema Silva, Jessica Cecilia (2020)
Writing, in turn, forces us to reflect before transmitting information, this process makes when we have to express ourselves orally our expressive capacity is enhanced. In this way we assimilate knowledge that enriches our language and helps us express ourselves both orally and in writing. This routine is important in early childhood education and should be encouraged from the first years of life. Specialists suggest doing it in a way that means a pleasure for children to marvel at the universe of knowledge and experiences that delivers a text or a story, whatever its type. Gradually, the ability allows you to learn things about the world around them. Reading, in particular, becomes a means of incalculable value to increase the desire to know. When early literacy interventions are provided in a systematic and research-based manner, the quality of the delivery of these interactions by the educator can vary greatly, and these variations seem to make a big difference in children's reading results. As we design policies and services for young children, aimed at reducing the risk of reading failures through prevention, we must ensure that the relationships and interactions children have with adults that provide the context in which they will increase the knowledge, skills and interests are of the highest quality